Crop Production and Global Environmental Issues - Hakeem, Khalid Rehman (London Springer Cham, 2015)
Agricultural production has been considered as the key sector for revitalization of the economy and well being of the people in any country. For decades, due to increasing food demand together with policies encouraging production, agricultural science has focused on boosting production through the development of new technologies. Agriculture has become increasingly intensive. Farmers are becoming capable of producing higher yields using less labor and less land due to many factors, including use of fertilizer, and pesticides, introduction of farm machinery, development of hybrid and genetically modified strains and increased knowledge about farm management practices. Intensification of agriculture has not, however, been an unmixed blessing because this success has come at a high environmental cost. The damaging effects of intensification of agriculture include water, air and soil pollution, as well as the loss of wildlife, habitats and landscape features. As agricultural sustainability means maintaining productivity while protecting the natural resource base, there is increasing general recognition of the need to improve environmental performance in agriculture, through enhancing the benefits and reducing the harmful environmental effects. The book 'Crop Production and Global Environmental Issues' is a very timely effort in this direction. It discusses the main environmental issues and challenges which affects the crop production and productivity throughout the globe, particularly in developing countries. The book also provides some solutions to cope up with such challenges.
Keywords: Agriculture; Climate change; Plant breeding; Agriculture; Climate Change/Climate Change Impacts; Plant Breeding/Biotechnology.